Agroforestry Management in Realizing Sustainable Farming Systems in Dry Lands of Dompu Regency from an Ontological Perspective - Yusuf, M.; Hemon, Farid; Sukartono, Sukartono (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Agroforestry management in dry land in Dompu Regency is important and strategic in efforts to improve resource sustainability and community welfare, namely by combining forestry and agricultural elements to create a sustainable and adaptive farming system to environmental changes. This paper aims to: (1) describe the concept and role of agroforestry in dry land farming; (2) analyze agroforestry management in realizing a sustainable farming system in Dompu Regency from an ontology perspective, and (3) analyze agroforestry models that can be developed in dry land farming in Dompu Regency. The method used in this study is a literature review: Data is analyzed descriptively. The results of the study indicate that: (1) Agroforestry is an integrated land management approach that integrates elements of forestry, agriculture, and livestock in one system to produce ecological and economic benefits simultaneously. (2) The application of agroforestry in Dompu Regency requires a multidimensional approach based on a comprehensive ontological understanding, covering physical and biological aspects, time dynamics, socio-economics, as well as axiological and epistemological dimensions; and (3) Several agroforestry models that have the potential to be developed in the dry land areas of Dompu Regency include: alley cropping (alley planting), silvopasture (combining trees and livestock), multistrata (tiered) systems, and intensive yard gardens. The selection of the right model must be adjusted to the biophysical characteristics of the land, the socio-economic conditions of the community, and the capacity of local institutions so that its implementation can run optimally and sustainably.